Postmortem radiologic and pathologic findings in COVID-19: The Toronto experience with pre-hospitalization deaths in the community. (May 2021) - Williams, Andrew S.; Dmetrichuk, Jennifer M.; Kim, Patrick; Pollanen, Michael S.
Highlights: Fatal COVID-19 pneumonitis can show changes on PMCT that may be useful to identify previously unrecognized cases. Fatal COVID-19 pneumonitis is characterized by diffuse alveolar damage, reactive pneumocytes and patchy chronic inflammation. SARS-CoV-2 in the nasopharynx does not prove fatal COVID-19 without proper clinical, radiologic, and pathologic correlation. Abstract: Over a year after the initial emergence of the disease, the COVID-19 pandemic continues to strain healthcare systems worldwide. The value of feedback and connection between clinical care, public health, and death investigation systems has never been more clear. To this end, knowledge of the radiologic and histopathologic features of fatal COVID-19 is critical for those working with the living and the dead. Most of the medical descriptions of COVID-19 are either focused on clinical in vivo medical imaging or autopsies performed following an intensive course of treatment over days to weeks prior to death, rather than deaths in the community prior to hospitalization. Here we report the postmortem computed tomography (PMCT) and lung histopathology in five fatal cases of COVID-19 that were subject to medicolegal death investigation. All individuals died in the community without medical treatment, or after a brief terminal admission to hospital. In these cases, the main PMCT findings included: diffuse lung changes including ground glass-type opacifications, a "crazy paving" appearance, variable areas of more dense consolidation, and relatively few areas of spared/less involved lung parenchyma. The unifying histopathology was diffuse alveolar damage in various stages of cellular evolution. In all cases, the pattern of PMCT and the lung histopathology corroborated the diagnosis of COVID-19. We propose the routine use of PMCT as a potential screening tool for the identification of COVID-19 related fatalities in the medicolegal setting where a paucity of historical information may not otherwise permit the identification of this disease prior to autopsy.